2021
DOI: 10.1016/j.socscimed.2021.113831
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of suicidal behaviour in men: A narrative synthesis of risk factors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 177 publications
(264 reference statements)
7
41
2
3
Order By: Relevance
“…Such markers of social disadvantage and health morbidity represent well-established risk factors for suicidal behaviour. A compelling body of evidence in the general population has demonstrated strong associations between risk of suicide and socioeconomic disenfranchisement, early-life adversity, trauma, physical illness, drug and alcohol abuse, psychiatric morbidity, and personality traits such as impulsivity and aggression ( Carrasco-Barrios et al, 2020 ; Fazel & Runeson, 2020; O’Connor & Nock, 2014 ; Richardson et al, 2021 ; Turecki et al, 2019 ). These vulnerability factors not only contribute to risk of criminal justice involvement but, given their overrepresentation in prisoners, may also account for the disproportionate prevalence of suicidal thoughts and behaviour within custodial settings.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Such markers of social disadvantage and health morbidity represent well-established risk factors for suicidal behaviour. A compelling body of evidence in the general population has demonstrated strong associations between risk of suicide and socioeconomic disenfranchisement, early-life adversity, trauma, physical illness, drug and alcohol abuse, psychiatric morbidity, and personality traits such as impulsivity and aggression ( Carrasco-Barrios et al, 2020 ; Fazel & Runeson, 2020; O’Connor & Nock, 2014 ; Richardson et al, 2021 ; Turecki et al, 2019 ). These vulnerability factors not only contribute to risk of criminal justice involvement but, given their overrepresentation in prisoners, may also account for the disproportionate prevalence of suicidal thoughts and behaviour within custodial settings.…”
Section: Risk Factorsmentioning
confidence: 99%
“…For example, linking men to debt management support or benefits advisors for financial difficulties and job loss. This is particularly important, as these types of issues are known to increase suicide risk in men (Richardson et al , 2021), and previous research has highlighted that this type of additional support is needed (Saini et al , 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of theory-driven models of suicidality and co-production are integral and distinguishing features of the JP model. Risk factors associated with male suicide are complex and diverse and subjected to temporal and context-related fluctuations (O’Connor and Kirtley, 2018; Richardson et al , 2021) highlighting the need for holistic approaches in suicide prevention interventions. The theory-driven nature of the JP model facilitates identification of the mechanisms underpinning the men’s suicidality enabling therapist to work alongside the men to adapt and tailor the JP model, creating a targeted intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Rasmussen and colleagues (2018) noted that "Suicide in men was connected to feelings of inadequacy and shame generated by not meeting the culturally dominating gender role ideals" (p. 328). Similarly, in a systematic review of the literature, Richardson et al (2021) found 119 commonly identified risk factors, many of which can apply to incels, including lower education levels, being single, living alone, being of short stature or of a specific ethnic group, negative life events or trauma, and depression. The incels.co (2020) survey reflects many of these risk factors.…”
Section: Suicidementioning
confidence: 99%